ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN UMKM DI SUKOHARJO - Lia Septiana; Pardi (PROSIDING, 2022)
This study aims to examine the effect of accounting, marketing, human resources, production and use of technology on the financial performance of MSMEs. The population in this study is the culinary MSMEs in Sukoharjo, amounting to 60.125 units. The error tolerance is set at 10% so that a sample of 100 respondents is obtained. The reseach data is obtained by giving questionnaires, then the data was analyzed using multiple linear regression analysis techniques. The test result show that the variables of accounting knowledge, marketing, human resources, production and technology have a simultaneous influence on financial performance with a significance value of 0,000 or < 0,05. These five independent variables affect financial performance by 57,2%. Keywords : Performance, Financial, MSMEs